EUROPEIZACJA PRAWA KARNEGO. TENDENCJE, PROBLEMY I ALTERNATYWY - Schiinemann, Bernd (Wydział Prawa i Administracji UAM, 2006)
The paper is divided into five parts. The Author presents the topics in the following order: the foreword, the introduction into the subject, the analysis of the principle of mutual recognition (taking the European Arrest Warrant and its consequences as an example, and focusing on those which are against the rule of law) and the disclosure of the deficiency of democratic legitimisation of European criminal law created by framework decisions. He also points out that there is a need to establish central European institutions in the area of criminal law enforcement and to present precise de lege ferenda postulates. This paper can be included among the critical trend of criminal law. The thesis presented in it are the outcome of the research which the author has conducted for several years. They are just a few postulates de lege ferenda and de lege lata. In order to grasp the whole spectrum o f the problem it is necessary to refer to other Prof. B. Schünemann’s publications in which the problems presented in the paper occupy a very important place.
EUROPEANISATION OF CRIMINAL LAW: TENDENCIES, PROBLEMS AND ALTERNATIVES